2021
DOI: 10.1111/odi.13789
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and depression in pregnant women: The role of oral health self‐perception as mediator

Abstract: Objective This study investigated the role of oral health self‐perception as mediator of association between dental caries and depression among pregnant women from the 2015 Pelotas Birth Cohort Study, Brazil. Materials and Methods Overall, 2,496 pregnant women participated of this oral health sub‐study. Data related to demographic and socioeconomic conditions, lifetime and current depression, and oral health self‐perception were collected. Participants were also assessed for dental caries (DMF‐T index). Depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Generally, these results were in harmony with many studies (22,26) that prove an inverse relationship between caries incidence and psychological satisfaction. Moreover, it came compatible with the study of Cademartori et al, 2021 (49) who observed that the presence of moderate/severe depressive signals and symptoms was higher in subjects with dental caries experience.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, these results were in harmony with many studies (22,26) that prove an inverse relationship between caries incidence and psychological satisfaction. Moreover, it came compatible with the study of Cademartori et al, 2021 (49) who observed that the presence of moderate/severe depressive signals and symptoms was higher in subjects with dental caries experience.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the most prevalent oral manifestations, listed in order of decreasing frequency, were caries, which were identified in 13 studies [4,8,9,22,[26][27][28]30,[32][33][34][35][36]; followed by periodontitis in 10 studies [4,8,12,23,[28][29][30]32,33,36]; and gingivitis in 7 studies [8,12,25,30,31,34,35]. Furthermore, pyogenic granuloma was observed in four studies [3,21,26,35] and candidiasis was noted in two studies [26,27].…”
Section: Prevalence Of Manifestationsmentioning
confidence: 87%
“…Four cohort studies [12,[21][22][23], fourteen cross-sectional studies [8,9,[24][25][26][27][28][29][30][31][32][33][34][35], one longitudinal study [4], and one case-control study [36] were included, as shown in Table 1.…”
Section: Types Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the sugar-rich diet has an influence on the bacterial load, its’ direct effect are dental caries, a common and costly disease in pregnant women [ 15 ]. Findings of the researchers from Pelotas show the far effect of dental caries in this group of patients, discussing that even depression is mediated by self-perception about oral health [ 16 ]. The authors show that the presence of depressive signals and symptoms was higher in pregnant women with dental caries experience, diverse severity of untreated dental caries, tooth loss, and filled tooth [ 16 ].…”
Section: Introductionmentioning
confidence: 99%